Citrus aphids in Italy: historical review - Addante R.; Djelouah K.; D'Onghia A.M. (Citrus tristeza virus and Toxoptera citricidus: a serious threat to the Mediterranean citrus industry, 2009)
Aphids occurring on citrus in Italy have been studied since the second half of the XIX century. Most of the previous papers on the aphids of the Italian citrus groves concerned faunistic and morphological traits whereas the main aspects investigated in the last decades focused on their potential as virus vectors and on tools and strategies used for their control. Eleven are the aphid species reported on citrus in Italy, although most of them can be found only occasionally. The following review takes also into account the works by Authors who have described some aspects relating to the morphology, biology, control, etc. of one or of several citrus aphid species in Italy.